Mediating Power-to-X: A case study of green imaginaries and environmental conflicts in local Danish news media - Horsbøl Anders (Nordicom Review)
Recently, Power-to-X (PtX) has come to play a prominent role in the public discussion of a green energy future, with high hopes expressed by political and business players. In the Danish news media, PtX has experienced a steep rise in attention, which calls for studies of how PtX is made sense of as a societal, not only a technological, phenomenon. Informed by the notion of sociotechnical imaginaries, this article investigates the local introduction of PtX in Frederica, one of the forerunner towns for PtX in Denmark, as represented in the coverage of the daily newspaper Fredericia Dagblad. The study analyses how PtX is made sense of by being connected to local actors, circumstances, and imagined futures. Two diverging sociotechnical imaginaries are identified, centring on 1) local (business) cooperation for green energy solutions towards a PtX adventure, and 2) concerns for scarce nature in a densely industrialised area. The findings show both similarities with and differences to already known mediatised environmental conflicts and point to dynamics between media, market, politics, and civil society in future mediatised environmental conflicts.